The World of Spirit Pacification: Issues of State and Religion - Kuroda, Toshio (Japanese journal of religious studies, 1996)
This essay examines the role of "spirit pacification" (chinkon) in Japanese history, focusing on developments in the medieval period. It begins with a historical sketch of the cults of vengeful spirits (goryō), examines how the exoteric-esoteric system (kenmitsu taisei) managed these cults, and concludes with comments on the relevance of this topic with regard to Shinto in contemporary Japan and the "Yasukuni Problem."